Gendered truth?: Analyzing the inclusion of gender-based violence across truth commissions - Anania, J (2023)
Truth commissions are increasingly prolific, contending with periods often marred by gender-based violence. Yet, despite an ‘empirical turn’ in transitional justice study, there was – until now – no cross-national data on truth commissions’ inclusion of gender violence. Using my newly created Gender Violence in Truth Commissions (GVTC) database, which tracks all references to gender violence across 50 truth commission final reports, I investigate how truth commissions have addressed gender-based violence. Although each empirical chapter pursues a unique line of enquiry, all four engage broadly with this question, addressing two key themes: what truth commissions have done and opportunities for expansion. In this work, I contribute novel data in the form of the GVTC database and provide an unprecedented cross-national understanding of gender-based violence inclusion across the full sample of truth commission cases. In doing so, I lay the foundation for future study and provide a new and valuable resource to researchers, policymakers and practitioners.